Mycenaean Messenia and the kingdom of Pylos - Simpson, R. Hope (Prehistory monographs, 2014)
This study outlines the state of our present knowledge concerning the Mycenaean settlements in Messenia and examines the evidence for reconstructing the political geography of the ""Kingdom"" of Pylos. The progress of archaeological exploration in Messenia is reviewed in relation to the Mycenaean (Late Helladic [LH]) period. The data from excavations and surveys concerning the Mycenaean settlements in Messenia are summarized. The author attempts to determine the extent of the ""Kingdom"" and to identify the locations of its main districts by correlating the archaeological data from Mycenaean sites with the the inscriptions in Linear B found in the "Palace of Nestor" at Ano Englianos.